Pemberdayaan Petani Melalui Pemberian Dana Bantuan Sosial In-cash Transfer Kepada Kelompok Tani Dalam rangka Optimasi Lahan Sawah di Kabupaten Minahasa - Palandeng, Dolf Heymans (JURNAL ILMIAH SOCIETY, 2015)
In agricultural development, which became one of the main problems, especially for the farmers is the lack of capital. One attempt to overcome these problems the government is to provide social assistance to the petani.Tujuan of this study examines the Farmer Empowerment Through Social Assistance Fund Granting In-Cash Transfers To Farmers Group Optimization in the Context of Wetland In Minahasa.Based on the results of this study concluded that social assistance In-Cash Transfers To Farmers Group Optimization in the Context of Wetland In Minahasa can empower groups especially in strengthening capital, the provision and rehabilitation of agricultural infrastructure and facilities, institutional capacity building and human resource capacity as well as tackling poverty group of inability trying farmer so that the agricultural production process can still take place.Â Keywords: Farmer Empowerment Fund, Social Assistance